Adaptasi Sosial Budaya Masyarakat Sasak Terhadap Keberadaan Sirkuit Mandalika Di Kabupaten Lombok Tengah Nusa Tenggara Barat - Ilhami Rifki; Sumilih, Dimas Ario (Jurnal Ekonomi dan Riset Pembangunan, 2024)
This research aims to find out: (1) The process of adaptation of the Sasak community in Lombok, West Nusa Tenggara to the existence of the Mandalika Circuit, (2) Forms of socio-cultural adaptation of the Sasak community in Lombok, West Nusa Tenggara to the existence of the Mandalika Circuit, and (3) Changes in behavior in the socio-cultural context of the Sasak community in Lombok after the existence of the Mandalika Circuit. This research uses a qualitative approach with descriptive research type, data collection techniques using observation, interview and documentation methods. The results of the study show: (1) The Sasak community in Central Lombok Regency, West Nusa Tenggara carries out the adaptation process at two main levels, namely social adaptation and cultural adaptation, (2) The form of socio-cultural adaptation seen in the community consists of four main forms, namely, language adaptation, livelihood system adaptation, social interaction adaptation and social group adaptation, and (3) Changes in behavior in the socio-cultural context are only seen in changes in the pattern of interaction between individuals in the community, especially people who are around the Mandalika Circuit and generally people who work and depend on the tourism industry, namely changes in daily language or formal language.